2022
DOI: 10.1039/d2en00629d
|View full text |Cite
|
Sign up to set email alerts
|

Water reduction on the facets of Fe(OH)2: an experimental and DFT study

Abstract: H2 production during the transformation of Fe(OH)2 into magnetite (i.e., Schikorr reaction), has a significant impact on many environmental applications, including the long-term effectiveness of permeable reactive barriers composed of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In experiments, layered bulk materials Co­(OH) 2 and Fe­(OH) 2 with similar structures have already been synthesized, and thus, there is a great possibility of attaining the monolayer limitation of Fe­(OH) 2 . In our calculations, we also compared the total energies of the Fe­(OH) 2 monolayer in phases H and T and found that the former is 22 meV per unit cell lower than the latter.…”
mentioning
confidence: 99%
“…In experiments, layered bulk materials Co­(OH) 2 and Fe­(OH) 2 with similar structures have already been synthesized, and thus, there is a great possibility of attaining the monolayer limitation of Fe­(OH) 2 . In our calculations, we also compared the total energies of the Fe­(OH) 2 monolayer in phases H and T and found that the former is 22 meV per unit cell lower than the latter.…”
mentioning
confidence: 99%
“…To understand the possible mechanism of structural carboxyl defect sites promoting photocatalytic H 2 production of g‐C 3 N 4 , density‐functional theory (DFT) calculations were performed to understand the influence of carboxyl group defects on the band structure and electronic features of the carboxyl‐defect endowed g‐C 3 N 4 (H 2 ‐O 2 ‐pCN). [ 40 ] The calculated bandgap of H 2 ‐O 2 ‐pCN is lower than the original g‐C 3 N 4 due to the formation of an intermediate transition level ( Figure ). More importantly, the electronic structure was optimized greatly, as reflected by the charge distribution map of H 2 ‐O 2 ‐pCN, which obviously provided local asymmetric electron environment to promote the migration of electrons, thus served as H 2 evolution active center.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed a W 2 C/W 2 N (WCN) particles modified ultrathin g-C 3 N 4 nanosheet Schottky junction via heterointerface engineering as shown in Figure 14, with the average size of tungsten carbide/ tungsten nitride (WCN) particles measured to be about 200 nm. [143] Based on the diffuse reflectance spectra obtained for the WCN particles modified g-C 3 N 4 composites (WCN/CN-25% in Figure 15a), it was obvious that the incorporation of WCN particles modified g-C 3 N 4 showed a red-shift in absorption edge (from 423 to 431 nm) and enhanced the visible light responsive-ness (400-800 nm). The estimated band gap of g-C 3 N 4 and WCN/CN-25% composites were around 2.72 and 2.66 eV, respectively (Figure 15b).…”
Section: S-scheme G-c 3 N 4 Nanosheets Heterostructure Nanoarchitecto...mentioning
confidence: 96%
“…The flat band potentials of g-C 3 N 4 and WCN/CN-25% (obtained through Mott-Schottky plots in Figure 15c) measured to be around À 0.89 and À 0.63 V, respectively, and the change in Fermi levels of the composite material is attributed to the incorporation of WCN particles in g-C 3 N 4 . [143] In this WCN particles modified g-C 3 N 4 Schottky junction system, WCN particles work as the electron mediator to accept photogenerated electrons from the conduction band of g-C 3 N 4 (Figure 15d). [144][145][146][147][148][149][150] A drastically increase H 2 generation efficiency was observed for the WCN particles modified g-C 3 N 4 Schottky junction with no Pt co-catalyst addition (1024.6 μmolg À 1 h À 1 , which was about 165 times of that of pristine g-C 3 N 4 ).…”
Section: S-scheme G-c 3 N 4 Nanosheets Heterostructure Nanoarchitecto...mentioning
confidence: 99%
See 1 more Smart Citation